Personalized medicine with drugs targeting the underlying protein defect in cystic fibrosis: is monitoring of treatment response necessary?. (July 2022) - Niedermayr, Katharina; Gasser, Verena; Rueckes-Nilges, Claudia; Appelt, Dorothea; Eder, Johannes; Fuchs, Teresa; Naehrlich, Lutz; Ellemunter, Helmut
Cystic fibrosis (CF) is caused by two mutations in the Cystic Fibrosis Transmembrane Conductance Regulator ( CFTR ) gene. In the last years, drugs targeting the underlying protein defect like lumacaftor/ivacaftor (LUM/IVA) or tezacaftor/ivacaftor (TEZ/IVA) and more recently elexacaftor/tezacaftor/ivacaftor (ELX/TEZ/IVA) were admitted. Outcome parameters evaluating therapy response like forced expiratory pressure in 1 s (FEV1 ), body mass index (BMI) or the efficacy of CFTR function in sweat glands showed improvement in several cases. Other, CFTR biomarkers were analysed rarely. This prospective observational study was aimed at evaluating CFTR function in patients treated with different CFTR modulators together with common valid clinical outcome parameters at standardized appointments (day 0, week 2, 4, 16). We followed four patients with the same mutation ( F508del-CFTR ), sex, age and disease severity. Monitoring focused on lung function, gastrointestinal aspects and CFTR function of sweat glands, nasal and intestinal epithelium. Sweat tests were performed by pilocarpine iontophoresis. Nasal potential difference (NPD) measured transepithelial voltage in vivo and potential increased when CFTR function improved. Rectal biopsies were obtained for intestinal current measurements (ICM) ex vivo . Intestinal CFTR function was assessed by stimulating chloride secretion with different reagents. Response to CFTR modulators regarding clinical outcome parameters was rather variable. A sweat chloride reduction of 35.3 mmol/L, nasal CFTR rescue of 4.4% and fivefold higher CFTR function in the intestine was seen at week 16 post-LUM/IVA. Due to our monitoring, we identified a non-responder to LUM/IVA and TEZ/IVA. In case of ELX/TEZ/IVA, clinical parameters and CFTR bioassays improved and were concordant. Although our cohort is small, results emphasize that non-responders exist and conclusions could not be drawn if patients were not monitored. Data on CFTR function can confirm or disprove ongoing CFTR dysfunction and might be helpful selectively. Non-responders need other alternative therapy options as demonstrated with ELX/TEZ/IVA.